Edukasi Tentang Pentingnya Kebugaran Jasmani dan Manajemen Emosi dalam Mendukung Perolehan Prestasi Olahraga - Gilang Nuari Panggraita; Mega Widya Putri; Syavira Nooryana; Idah Tresnowati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Student sports achievements is not only determined by physical ability, but also by the balance of physical fitness and emotional management. At SMA N 1 Bojong, students in the Special Sports Class (KKO) still face challenges such as such as a lack of understanding of targeted physical fitness, low awareness of healthy lifestyles, and suboptimal emotional regulation. These issues may affect their athletic performance and achievement potential. This community service program aims to provide comprehensive education on the importance of physical fitness and emotional management in supporting sports achievements. The program is expected to increase students’ understanding, reduce injury risks, enhance focus, and build mental resilience among KKO students. The outreach activity was conducted by lecturers and university students in one day and covered two main aspects, namely education on physical fitness and emotional management. The activity applied a participatory approach that actively involved students in theoretical learning, practical sessions, and evaluation through pre-test and post-test assessments. Based on the results, the average pre-test score was 70.7 and the average post-test score was 95.7, indicating an improvement in students’ understanding of both physical fitness and emotional management. It can be concluded that this community service activity successfully improved students’ comprehension regarding physical fitness and emotional management as key factors that support sports achievement. In addition to increasing knowledge, this program also instilled positive values so that students can become athletes who are physically healthy, emotionally intelligent, and strong in character.